Efecto de la adición de un suelo lacustre o ceniza volante en las propiedades de concretos hidráulicos - Martínez-Hernández, A.; Montes-García, Pedro; Moreno, E.; Fernández-González, A. (Revista ALCONPAT, 2011)
This investigation evaluated the addition of a lakeside soil or fly ash as a supplementary material in the properties of ordinary and high strength concretes. The replacement levels were of 20% for both materials, while the fly ash was also used at 40%. The tests in the fresh condition included slump, temperature, volumetric weight and air content; while on the hardened state the tests included compressive strength and reactivity index after 1, 3, 7, 13, 28, 56 and 90 days. The coefficient of chlorides penetration was also analyzed. The results indicated that the lakeside soil did not show a noticeable effect on the fresh state characteristics of the concrete; nonetheless, on the hardened state, it reduced the strength and favored the penetration of chlorides.Keywords: high strength concrete; activity index; suplementary materials.